A Matter of Energy A Conversation with Nick Lane. - Burton, Howard (Ideas Roadshow Conversations Ser., 2020)
This book is based on an in-depth filmed conversation between Howard Burton and Nick Lane, Professor of Evolutionary Biochemistry at University College London and bestselling author. After an inspiring story of Nick Lane's career path, this wide-ranging conversation covers his bioenergetic view of early, evolutionary history, the origin of life and how all complex life is composed of a very particular cell type that we all share, and more. This carefully-edited book includes an introduction, The Big Picture, and questions for discussion at the end of each chapter. Howard Burton was the Foundin.